Real-time dual visualization of two different modalities for the evaluation of vocal fold vibration – Laryngeal videoendoscopy and 2D scanning videokymography: Preliminary report. Issue 2 (April 2017) - Kim, Geun-Hyo; Wang, Soo-Geun; Lee, Byung-Joo; Park, Hee-June; Kim, Yong-Cheol; Kim, Hyung-Soon; Sohn, Keon-Tae; Kwon, Soon-Bok
Abstract: Objective: Currently, various tools have been introduced for the assessment of vocal fold vibration: laryngeal videolaryngoscopy (LV), videokymography (VKG), high speed videoendoscopy (HSV), digital videokymography (DKG), and 2D scanning videokymography (2D VKG). Among these, the authors have recently designed a dual modality examination system using LV and 2D VKG for more detailed information regarding the vibrations of the vocal folds. The clinical availability of this hybrid system offers medical imaging departments a range of potential advantages in the evaluation of vocal fold vibration. The obvious benefit of simultaneous acquisition is the improved integration of information that allows not only optimal anatomic localization, but also physical movement patterns. Other advantages include the lessened inconvenience to patients due to no longer requiring repeated examinations and shortening the examination time, and increased profitability. The purpose of study was to identify the efficacy of real-time dual examination of two different modalities for the evaluation of vocal fold vibration in human subjects and vocal fold vibration simulator. Methods: One vocally healthy subject and three patients with vocal fold nodules, a vocal cyst, and vocal fold paralysis took part in this study. The vibratory patterns of the vocal folds were visualized using simultaneous real-time examination of two different modalities. Additionally, qualitative and quantitative analyses of the dual LV and 2D VKG images were performed. Results: Real-time dual examination using a two modality system provided high definition images of the vibratory movements of the vocal folds. By assessing the obtained images, we confirmed that the dual modality examination method was useful in the evaluation of pathologic vibratory patterns, even in non-periodic phonation. Conclusion: The present system might improve the understanding of the processes of vocal fold vibration and make a contribution to pathologic voice research, as well as clinical practice.